Rapid divergence of courtship song in the face of neutral genetic homogeneity in the cactophilic fly Drosophila buzzatii - Iglesias, Patricia Paola (2018)
A wide spectrum of song complexity has been documented in a broad range of animal taxa. However, the underlying processes shaping acoustic differences are still poorly understood. Empirical and theoretical studies suggest that different song parameters may be subject to different tempos and modes of evolution, resulting in a complex combination of stabilizing and directional selection that change among populations and through time. Nonetheless, the contribution of genetic drift to acoustic divergence is largely unexplored. In this study, we used the Q ST -F ST approach to investigate the relative role of selective and neutral processes in the evolution of courtship song in the cactophilic fly Drosophila buzzatii. We quantified variation in courtship song among 12 populations using flies reared under common-garden conditions. We found among-population divergence in courtship song parameters, but genetic homogeneity and no population structure. Using both mitochondrial DNA and microsatellite markers, we found evidence consistent with a role for directional selection causing song divergence. We discuss the statistical difficulties of detecting stabilizing selection as opposed to directional selection in our data. The role of song parameters in mate recognition and mate choice, and the role of sexual selection in song elaboration are also discussed.